2012
DOI: 10.1063/1.4733949
|View full text |Cite
|
Sign up to set email alerts
|

Scaled behavior of interface waves at an imperfect solid-solid interface

Abstract: Laser ultrasonic techniques allow the remote analysis of adhesion mechanisms at imperfect interfaces up to GHz frequencies. However, the sensitivity of interface waves to the properties of the contact is not very well known. In the present work, the mechanical boundary conditions are described considering that the contacting solid half-spaces are connected by tangential and normal springs. Such a modeling implies a discontinuity of the displacement field across the interface. To identify the relative amplitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…The bonding between two solid plates can be probed by various ultrasonic techniques: longitudinal and shear waves reflection or transmission at the interface, 1,2 thickness resonances, 3 ultrasonic guided waves propagating along the interface. [4][5][6][7][8] All these methods require a modelisation of the ultrasonic wave interaction with the interface supposed homogeneous. 9 Recently it was shown that Zero-Group Velocity (ZGV) Lamb modes associated with laser ultrasonic techniques, allow a local and non contact measurement of mechanical properties of isotropic or anisotropic plates and shells.…”
mentioning
confidence: 99%
“…The bonding between two solid plates can be probed by various ultrasonic techniques: longitudinal and shear waves reflection or transmission at the interface, 1,2 thickness resonances, 3 ultrasonic guided waves propagating along the interface. [4][5][6][7][8] All these methods require a modelisation of the ultrasonic wave interaction with the interface supposed homogeneous. 9 Recently it was shown that Zero-Group Velocity (ZGV) Lamb modes associated with laser ultrasonic techniques, allow a local and non contact measurement of mechanical properties of isotropic or anisotropic plates and shells.…”
mentioning
confidence: 99%
“…Two different types of modes, symmetric and antisymmetric, may propagate along the interface; the symmetric wave has a critical frequency below which its speed reaches the transverse wave velocity in the substrates and it becomes leaky [4,5]. It was also reported that interface waves can sense imperfect bonded interfaces and their velocities and attenuations reflect the degree of the interface imperfection [6][7][8][9]. To better understand the propagation behavior of the interface waves optical interferometric visualization techniques are useful when applied to transparent solids [2].…”
Section: Introductionmentioning
confidence: 96%
“…Many authors have utilized Rayleigh waves to generate the interface wave [6][7][8][9][10]. In this case, the interface wave is produced at an upward step corner.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of adhesion can be probed by surface acoustic waves (SAWs) if the elastic properties are known. 6,7 The aim of this paper is, therefore, to estimate a value for the Young's modulus and porosity of a MnO 2 coating.…”
Section: Introductionmentioning
confidence: 99%